1993
DOI: 10.1108/09566169310043124
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Occupational Health: The Asia – Pacific Region

Abstract: The Asia‐Pacific Region is the fastest growing area of the world in economic terms. Unfortunately, it has also suffered from several environmental and occupational health problems largely as a result of this rapid growth without attendant safeguards. Highlights problems such as environmental pollution, those relating to sanitation, cigarette smoking, traffic accidents, poisoning from industrial and agricultural chemicals, noise, health of women workers and other psychosocial problems, and recent trends in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…A collaborative study conducted in four such countries showed reported rates per 1,000 agricultural workers as 13.3 for Indonesia, 132.8 for Malaysia, 45.7 for Sri Lanka and 81.3 for Thailand. Organophosphate compounds were the most frequently responsible pesticides in Indonesia, Malaysia and Sri Lanka (Phoon, 1993).…”
Section: Pesticidesmentioning
confidence: 99%
“…A collaborative study conducted in four such countries showed reported rates per 1,000 agricultural workers as 13.3 for Indonesia, 132.8 for Malaysia, 45.7 for Sri Lanka and 81.3 for Thailand. Organophosphate compounds were the most frequently responsible pesticides in Indonesia, Malaysia and Sri Lanka (Phoon, 1993).…”
Section: Pesticidesmentioning
confidence: 99%
“…Four countries, Thailand, Malaysia, Sri Lanka and Indonesia, participated. The third research project focused on small-scale industries in the Philippines, Korea, Hong Kong and Singapore (Phoon, 1992).…”
Section: Asian Association Of Occupational Healthmentioning
confidence: 99%